Measurements of continuum lowering in solid-density plasmas created from elements and compounds - O. Ciricosta (Nature Portfolio, 2016)
The effect of dense plasma environment on the energy levels of an ion is usually described in terms of a lowering of its continuum level. Here the authors present an isochoric-heating experiment to measure and compare continuum lowering in single-species and mixture plasmas to provide insights for models.